Comparative Evaluation of Satellite Measured Data with Ground Measured Data for Five Selected Rainfall Stations in Southwestern Nigeria - Mayowa A. OGIDI; Sunday O. OYEGOKE; Olayiwola A. AKINTOLA, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Accurate rainfall data is essential for hydrological applications, yet ground-based measurements remain sparse and irregularly distributed, particularly in developing countries. Satellite-derived precipitation estimates offer an alternative, but their accuracy must be validated before use. This study evaluates the agreement between ground-observed rainfall data from the Nigerian Meteorological Agency (NIMET) and satellite-derived data from POWER NASA across five stations in southwestern Nigeria (Abeokuta, Osogbo, Ibadan, Ikeja, and Akure) from 2002 to 2012. Descriptive statistical analyses, including mean, standard deviation, skewness, and kurtosis, were used to compare both datasets. The findings indicate that while POWER NASA generally records slightly higher mean rainfall values in most locations, NIMET data exhibit greater variability. The correlation coefficient (CC) between the datasets varies across stations, with the highest values recorded in Abeokuta (0.51) and Osogbo (0.50), indicating a moderate relationship, while other locations, particularly Akure (0.27), show weak correlations. These results suggest that satellite estimates may not fully align with ground observations due to factors such as; sub-cloud evaporation, seasonal variations, and localized precipitation patterns not captured by satellite sensors. The study suggests further validation before using satellite-derived rainfall data for critical hydrological applications in the region.